CHAPTER 4 SYNTHETIC CLAY MINERALS AND PURIFICATION OF NATURAL CLAYS - Carrado K.A.; Decarreau A.; Petit S.; Bergaya F.; Lagaly G. (My University, 2006)
A subjective differentiation can be made between the formation of clay minerals in their natural, geologic environment such as in soils, and the synthesis of pure minerals in a controlled, laboratory environment. The former point would be of interest to the geochemist, soil scientist, or mineralogist, whereas the latter materials are prepared to exploit a clay mineral’s unique structure and/or surface chemistry for some particular application.